Implementasi Metodologi Scrum dalam Pengembangan Vehicle Inspection Mobile Application Divisi CIST PT. Serasi Autoraya - Hartanto, Rosa (JATISI, 2024)
In developing information systems there are several methodologies, one of them is scrum which is included in the agile category. This method is considered capable of producing high quality software that suits user needs, and can be applied to projects with long or short work durations. Scrum is adaptive, flexible, fast in making changes and has systematic and repeatable stages. With this method, the results of a sprint can be achieved in a relatively brief period. So that the results of the previous sprint can be evaluated more quickly and if there are results that are not suitable then improvements can be made immediately, where these improvements will be carried over to the next sprint until results are obtained that meet requirements. Based on the results and observations, the use of the Scrum methodology in developing the Vehicle Inspection Mobile Application has proven to be effective in handling changing needs during the application development period, where by repeating reviews each sprint it is able to produce an application that meets user requests and expectations.